Impact of the MTHFR C677T polymorphism on blood pressure and related central haemodynamic parameters in healthy adults. Issue 4 (27th July 2022) - Rooney, Martina; Hughes, Catherine F.; Strain, J. J.; Clements, Michelle; McNulty, Helene; Ward, Mary
Abstract: Background: The C677T polymorphism in the gene‐encoding methylenetetrahydrofolate reductase (MTHFR) is associated with an increased risk of hypertension and cardiovascular disease. Riboflavin, the MTHFR cofactor, is an important modulator of blood pressure (BP) in adults homozygous for this polymorphism (TT genotype). The effect of this genetic variant on BP and related central haemodynamic parameters in healthy adults has not been previously investigated and was examined in this study. Methods: Brachial BP, central BP and pulse wave velocity (PWV, SphygmoCor XCEL) were measured in adults aged 18–65 years prescreened for MTHFR genotype. Riboflavin status was assessed using the erythrocyte glutathione reductase activation coefficient assay. Results: Two hundred and forty‐two adults with the MTHFR 677TT genotype and age‐matched non‐TT (CC/CT) genotype controls were identified from a total cohort of 2546 adults prescreened for MTHFR genotype. The TT genotype was found to be an independent determinant of hypertension ( p  = 0.010), along with low‐riboflavin status ( p  = 0.002). Brachial systolic and diastolic BP were higher in TT versus non‐TT adults by 5.5 ± 1.2 and 2.4 ± 0.9 mmHg, respectively (both p  < 0.001). A stronger phenotype was observed in women, with an almost 10 mmHg difference in mean systolic BP in TT versus non‐TT genotype groups: 134.9 (95% confidence interval [CI] 132.1–137.6) versus 125.2 (95% CI 122.3–128.0) mmHg; p  < 0.001. In addition, PWV was faster in women with the TT genotype ( p  = 0.043). Conclusion: This study provides the first evidence that brachial and central BP are significantly higher in adults with the variant MTHFR 677TT genotype and that the BP phenotype is more pronounced in women. Abstract : When stratified by MTHFR genotype women with TT had a systolic blood pressure of almost 10 mmHg higher than their non‐TT counterparts. Furthermore, the TT genotype was associated with higher brachial Mean Arterial Pressure and Pulse Pressure in women. Key points: This is the first study to show that central blood pressure is significantly higher in younger adults with the variant MTHFR 677TT genotype compared to those with the CC/CT genotypes providing further evidence for the role of this genetic risk factor in hypertension. Furthermore, the BP phenotype and pulse wave velocity appear to be more pronounced in women compared to men. Riboflavin, the cofactor for the MTHFR enzyme, was found to be an important modulator of blood pressure, with suboptimal riboflavin status almost doubling the risk of hypertension. These data have relevance for public health given that riboflavin has been shown to lower blood pressure specifically in individuals with the MTHFR TT genotype. Given the high prevalence of the MTHFR C677T polymorphism globally, these findings have important implications for the prevention and treatment of hypertension in adults worldwide with this genetic risk factor.